A Microwave Holographic Procedure for Large Symmetric Reflector Antennas Using a Fresnel-Zone Field Data Processing. (19th March 2012) - Mazzarella, Giuseppe; Montisci, Giorgio; Serra, Giampaolo
Abstract : In this paper we propose a new holographic procedure for the diagnostic of large reflector antennas, based on the direct use of the Fresnel-field pattern. The relation leading from the Fresnel field to the current on the reflector surface is formulated in the least-squares sense as a discrete data inverse problem and then regularized by using a singular value decomposition approach. A detailed theoretical analysis of the problem and full assessment of the presented technique are provided. Simulations are carried out by using the radiative near-field pattern generated with a commercial software. Results show good accuracy and robustness to noise for the retrieval of the panel-to-panel misalignment of a reflector antenna.